Fuzzy based decision support method for selection of sustainable wastewater treatment technologies - Kamami, Martin Igecha; Ndegwa, George M.; Home, Patrick G. (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: Inadequate decision support tools have led to selection of inappropriate wastewater treatment technologies. The objectives of this research were to investigate performance data for wastewater treatment technologies, develop a Decision Support Method (DSM) for evaluating performance of technologies, and to validate the developed method. The method was developed through evaluation of performance of wastewater treatment technologies against environmental and economic indicators. Fuzzy logic techniques in form of linguistic variables were applied in order to support decision making under uncertainty. The DSM relied on performance evaluation in order to rate effectiveness of wastewater treatment technologies. DSM was validated through a training tool in ED-WAVE, a model developed by a consortium of European and Asian countries. The reliance of the DSM on performance evaluation was an improvement on the existing decision support tools such as ED-WAVE that relied on retrieval of past performance data. As DSM integrated environmental and economic factors in evaluating wastewater treatment technologies, it was thus able to select a process that was not only environmentally sustainable but also economically affordable. Keywords: decision support method, wastewater treatment technologies, environmental indicators, performance rating, fuzzy logic, ED-WAVE DOI: 10.3965/j.issn.1934-6344.2011.01.041-051 Citation: Martin I. Kamami, George M. Ndegwa, Patrick G. Home. Fuzzy based decision support method for selection of sustainable wastewater treatment technologies. Int J Agric & Biol Eng, 2011; 4(1): 41<span style="font-size: 9pt; line-height: 140%; font-family: